The status of pediatric surgery in Malawi: a narrative mini-review - Flocks Monaghan, Celina; Pittalis, Chiara; Byrne, Elaine; Hussein, Israa; Chilunjika, Tiyamike; Nandi, Bip; Borgstein, Eric; Gajewski, Jakub (Frontiers in Pediatrics, 2023)
Introduction Pediatric surgery is essential to a well-functioning health system. Unmet surgical needs contribute to 6.7% of pediatric deaths in Malawi. Understanding the current state of pediatric surgical care in Malawi is necessary to recognize gaps and opportunities in service delivery and to develop evidence-based national planning and solutions. Methods This narrative mini review synthesized the literature on the state of pediatric surgery in Malawi through the pillars of the World Health Organization's Health System Building Blocks. A search of PubMed, Embase, and Scopus databases was executed to identify relevant studies and a thematic analysis was performed. Further, to ensure contextual accuracy, pediatric surgeons from Malawi were consulted and involved in this review. Results Twenty-six papers were identified. In Malawi's central hospitals, there are six specialist pediatric surgeons for a pediatric population of more than 8 million. There is limited pediatric surgical capacity at the district hospitals. There is little to no written evidence of the national governing and finance structures in place for pediatric surgical services. Discussion In countries like Malawi, where a significant portion of the population comprises children, it is crucial to recognize that pediatric services are currently inadequate and fall short of the required standards. It is crucial to prioritize the enhancement of services specifically designed for this age group. This review aims to shed light on the existing gaps within pediatric surgical services in Malawi, providing valuable insights that can inform the development of comprehensive national surgical planning strategies.